A framework for sustainable service system configuration: Exploring value paradoxes with examples from the hospitality industry. (15th August 2019) - Van Riel, Allard C.R.; Zhang, Jie J.; McGinnis, Lee Phillip; Nejad, Mohammad G.; Bujisic, Milos; Phillips, Paul A.
Abstract : Purpose: While innovative service systems may create substantial value for certain stakeholders, they often destroy value for others. This value paradox frequently leads to unsustainable service systems. The purpose of this paper is to explore the use of multiple theories to pinpoint and explain these value paradoxes, build a framework allowing potentially more sustainable value configuration of service systems and develop an agenda for future research. The framework is illustrated with examples from the hospitality industry. Design/methodology/approach: The paper draws on prevalent theories and approaches, including service-dominant logic, business modeling, transaction cost economics, stakeholder theory, configuration theory and set theory, to develop a value configuration framework. Findings: In a service system, the configuration of resources and relationships between these resources (i.e. the set of value propositions for various stakeholders of the system) determines which stakeholders will gain and which will lose and to what extent. For that reason, insight into the range of possible service configurations – or business models – will help decision makers consider the effects on various stakeholders, and, where possible, set their priorities right and make their businesses more sustainable. The research produces a rich research agenda. Research limitations/implications: Examples from hospitality allow an in-depth examination of a range of dynamic configurational and technological innovations, but some idiosyncratic characteristics of the context may impede the wider applicability of the conceptual framework. Future research could complement this work by studying other service sectors. Practical implications: The paper aims to provide decision makers in the service industry with a conceptual tool to explore, diagnose and, if needed, adjust the value configuration of their service operations. In practice, this tool may help explicate the service system configuration, thus helping managers determine their organizations' desired positioning in terms of value creation and destruction, and to choose strategic directions by adapting configurations. Social implications: Legislation and regulations are being adapted to various new service configurations. This paper attempts to – at least conceptually – distinguish different service configurations, allowing policy makers to identify the value trade-offs between stakeholders, including society at large. Originality/value: Previous research focused primarily on value creation by innovative services and business models. Value creation for one stakeholder, however, could lead to value destruction for another. Taking this paradox into consideration may result in more open service ecosystems that explicitly consider sustainability and value implications in multiple dimensions and for a broader group of stakeholders.